Macroeconomic Variables and the Indonesian Sharia Stock Index - Sudarsono, Heri; Latifatunnisa (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Macroeconomic development significantly impacts the movement of the Indonesian Shariah Stock Index (ISSI). This study analyzes the effects of five macroeconomic variables, namely exchange rate (ER), inflation (INF), BI Rate (BIRATE), oil price (OP), and money supply (MS) on ISSI using quantitative data from January 2015 to December 2022 and the Vector Error Correction Model (VECM) framework. The analysis revealed that in the short term, ER, INF, BIRATE, OP, and MS did not significantly affect ISSI. However, in the long-term, ER, BIRATE, OP, and MS significantly impact ISSI, whereas INF remains insignificant. Among these variables, ER and MS had the most substantial influence on ISSI. These findings underscore the importance of macroeconomic stability in shaping ISSI's long-term performance, providing valuable insights for policymakers and investors aiming to navigate the dynamic relationship between macroeconomic factors and Islamic financial markets. Maintaining macroeconomic stability is essential for supporting the growth and resilience of the Islamic financial market. Policymakers should focus on effectively managing exchange rates and money supply while fostering a stable economic environment to enhance ISSI performance.